Adverse drug reaction monitoring through active surveillance in the inpatients of general medicine ward of a tertiary care hospital - Pooja Roy; Pratibha Nadig; C A Jayashankar (Wolters Kluwer Medknow Publications, 2022)
Objective: To monitor and analyze the adverse drug reactions (ADRs) by active surveillance in the inpatients of the department of general medicine of a tertiary care hospital. Materials and Methods: This was a cross-sectional study on the patients aged 18-70 years conducted for a period of 6 months. Patients' medical history, any new symptoms after commencing treatment, and their details were obtained after direct interviews. The case report forms were also reviewed. Suspected ADRs were documented in consultation with the attending physicians. Descriptive statistics was used to analyze the data for the occurrence, relatedness to the drug, seriousness, preventability, severity, intensity, and predictability of ADRs. Results: Fifty-three women and 47 men consented to participate, the majority of whom were between the ages of 20 and 30 years. Thirty suspected ADRs were detected in 24 out of 100 patients. The most common indications for which the drugs were prescribed were depression, psychosis, bipolar disorder, atopic dermatitis, and cervical spondylitis. Of the 30 ADRs, 28 were probably related, and 2 were possibly due to the prescribed drugs. Seven ADRs were serious in nature. Four ADRs were definitely preventable, seven were probably preventable, and nineteen were not preventable. Maximum ADRs were caused by immunosuppressants including steroids. Dermatological reactions were the most common manifestations of ADRs followed by that of central nervous system. There were four rare ADRs, namely, escitalopram-induced duodenitis, phenobarbitone-induced pancytopenia, quetiapine-induced thrombocytopenia, and aripiprazole-induced ocular gyrus syndrome. ADRs were mostly mild to moderate in intensity. Conclusion: Monitoring the ADRs through active surveillance is helpful to get a detailed information and to detect rare ADRs.